1990
DOI: 10.1002/ana.410270305
|View full text |Cite|
|
Sign up to set email alerts
|

The diagnosis and treatment of cerebral mycotic aneurysms

Abstract: Seventeen patients were treated for 28 documented cerebral mycotic aneurysms. Initial neurological symptoms were attributable to aneurysm rupture in only 7 patients, and in 3 of them symptoms did not suggest subarachnoid hemorrhage. Six patients presented with embolic infarction and 1 with meningitis; in 3 patients it was uncertain if aneurysm rupture occurred. Four patients had rupture of at least one aneurysm while receiving appropriate antibiotic treatment and another had rupture at the conclusion of therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 67 publications
1
48
0
4
Order By: Relevance
“…The use of such therapy alone for the treatment of ICMA has variable success rates. 127,135,162,169,170,172 There are no controlled studies, but there are numerous anecdotal case reports on the natural history of unruptured ICMA treated with antibiotic drugs alone. 162,169,[173][174][175] Several studies reported successful healing of ICMA with antibiotic drugs alo ne.…”
Section: Antimicrobial Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of such therapy alone for the treatment of ICMA has variable success rates. 127,135,162,169,170,172 There are no controlled studies, but there are numerous anecdotal case reports on the natural history of unruptured ICMA treated with antibiotic drugs alone. 162,169,[173][174][175] Several studies reported successful healing of ICMA with antibiotic drugs alo ne.…”
Section: Antimicrobial Therapymentioning
confidence: 99%
“…127,135,162,169,170,172 There are no controlled studies, but there are numerous anecdotal case reports on the natural history of unruptured ICMA treated with antibiotic drugs alone. 162,169,[173][174][175] Several studies reported successful healing of ICMA with antibiotic drugs alo ne. 127,135,162,[175][176][177] Corr et al 178 reported 18 patients with ICMA treated with antibiotic drugs alone.…”
Section: Antimicrobial Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…2 A second study reported CMAs (10/20, 50%) that either resolved or disappeared and 10/20 (50%) demonstrated no change or enlargement while the patient was on antibiotic therapy. 17 A third study found that approximately 30%…”
Section: 3mentioning
confidence: 99%
“…IIAs can be treated with antibiotic therapy alone, with an unpredictable evolution: they can regress, enlarge, stabilize or even rupture 6 . In patients treated with surgery or, more recently, endovascular techniques (EvT), occlusion of the IIAs can be achieved 7,8 . We report five cases of IIAs associated with endocarditis, which were treated with endovascular techniques.…”
Section: Dr Eduardo Wajnberg -Rua Lopes Quintas 100 / 602 -22460-010mentioning
confidence: 99%